Interpretasi Simbolik Kendi Maling dalam Konteks Kehidupan Sosial Masyarakat Banyumulek Lombok Barat - Mi’rajus Subyan Rahmat; Bayu Aji Pamungkas; Muhammad Tomi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The kendi maling (maling jug) is a typical pottery artifact from Banyumulek Village, West Lombok, with a unique shape and symbolic meaning in the social life of the Sasak people. This study aims to uncover the symbolic interpretation of the kendi maling (maling jug) through Charles Sanders Peirce's semiotic framework, which includes the categories of icon, index, and symbol. The method used was descriptive qualitative, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that the kendi maling (maling jug) functions as an icon representing the continuity of craft traditions, as an index related to the values ​​of caution and traditional protection systems, and as a symbol reflecting the simplicity, ingenuity, and wisdom of the Banyumulek people. However, the modernization and commodification of pottery have caused a shift in meaning, with the younger generation increasingly disconnected from the philosophical values ​​contained in the artifact. This study emphasizes the importance of preserving the symbolic meaning of the kendi maling (maling jug) as part of efforts to maintain local cultural identity and support the sustainability of the Banyumulek craft tradition.